Sperm dynamics in spiders (Araneae): ultrastructural analysis of the sperm activation process in the garden spider Argiope bruennichi (Scopoli, 1772). - Oliver Vöcking; Gabriele Uhl; Peter Michalik (PLoS ONE, 2013)
Storage of sperm inside the female genital tract is an integral phase of reproduction in many animal species. The sperm storage site constitutes the arena for sperm activation, sperm competition and female sperm choice. Consequently, to understand animal mating systems information on the processes that occur from sperm transfer to fertilization is required. Here, we focus on sperm activation in spiders. Male spiders produce sperm whose cell components are coiled within the sperm cell and that are surrounded by a proteinaceous sheath. These inactive and encapsulated sperm are transferred to the female spermathecae where they are stored for later fertilization. We analyzed the ultrastructural changes of sperm cells during residency time in the female genital system of the orb-web spider Argiope bruennichi. We found three clearly distinguishable sperm conditions: encapsulated sperm (secretion sheath present), decapsulated (secretion sheath absent) and uncoiled sperm (cell components uncoiled, presumably activated). After insemination, sperm remain in the encapsulated condition for several days and become decapsulated after variable periods of time. A variable portion of the decapsulated sperm transforms rapidly to the uncoiled condition resulting in a simultaneous occurrence of decapsulated and uncoiled sperm. After oviposition, only decapsulated and uncoiled sperm are left in the spermathecae, strongly suggesting that the activation process is not reversible. Furthermore, we found four different types of secretion in the spermathecae which might play a role in the decapsulation and activation process.